Early Sunni historiography : a study of the Tarikh of Khalifa born Khayyat - Andersson, T. S. (Islamic History and Civilization, 2018)
In Early Sunnī Historiography , Tobias Andersson presents the first full-length study of the earliest Islamic chronological history extant: the Tārīkh ( Chronicle ) of the Basran ḥadīth scholar and historian Khalīfa born Khayyāṭ al-ʿUṣfurī (d. 240/854). The book examines how Khalīfa worked as a historian in terms of his social and intellectual context, selection of sources, methods of compilation, arrangement of material and narration of key themes in comparison to the wider historiographical tradition. It shows how Khalīfa's affiliation with the early Sunnī ḥadīth scholars of Basra is reflected in his methods and concerns throughout the Tārīkh , while also highlighting similarities to other histories compiled by ḥadīth scholars of the third/ninth century.